What makes (hydroxy)chloroquine ineffective against COVID-19: insights from cell biology. (9th March 2021) - Altulea, Dania; Maassen, Sjors; Baranov, Maksim V; van den Bogaart, G
Abstract: Since chloroquine (CQ) and hydroxychloroquine (HCQ) can inhibit the invasion and proliferation of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in cultured cells, the repurposing of these antimalarial drugs was considered a promising strategy for treatment and prevention of coronavirus disease (COVID-19). However, despite promising preliminary findings, many clinical trials showed neither significant therapeutic nor prophylactic benefits of CQ and HCQ against COVID-19. Here, we aim to answer the question of why these drugs are not effective against the disease by examining the cellular working mechanisms of CQ and HCQ in prevention of SARS-CoV-2 infections.